REPRESENTASI PARIWISATA BALI MELALUI KOMODIFIKASI TARI KECAK DI PURA LUHUR ULUWATU : REPRESENTATION OF BALI TOURISM THROUGH COMMODIFICATION OF KECAK DANCE AT PURA LUHUR ULUWATU - Anggraeni Purnama Dewi; Syarah Nurul Fazri (PT. RANESS MEDIA RANCAGE, 2025)
The development of tourism has a considerable influence on the performing arts in Bali, and the Kecak Dance at Uluwatu Temple is no exception. The title of this article is “Representation of Bali Torism Through Commodification of Kecak Dance at Pura Luhur Uluwatu”. This article reveals how the relationship between the traditional performing arts of a religious nature that was originally only offered for religious rituals, but now becoming commercially valuable tourism industry, that can be displayed freely to the tourists. This is based on the fact that the Bali island often becomes the main purpose of the tourists, both local and foreign tourist, so that Balinese artists are highly demanded to have creativity to package the traditional art into commercially valuable tourism art. The method used in this research is a qualitative method with descriptive presentation. The researcher get data based on study literature and observation. The results show that there has been a change in the function of the Kecak Dance at Pura Luhur Uluwatu, which was originally religious and sacred, has now changed the function to commercial value after going through commodification to support the tourism industry.